Plasma phytoestrogens concentration and risk of colorectal cancer in two different Asian populations. Issue 5 (October 2018) - Ko, Kwang-Pil; Yeo, Yohwan; Yoon, Ji-Hye; Kim, Cheong-Sik; Tokudome, Shinkan; Ngoan, Le Tran; Koriyama, Chihaya; Lim, Young-Khi; Chang, Soung-Hoon; Shin, Hai-Rim; Kang, Daehee; Park, Sue K.; et al.
Summary: Background & aims: To evaluate the relationship between phytoestrogen and colon cancer risk, we quantified plasma isoflavones (Genistein and Daidzein) and lignan (enterolactone) in a Korean nested case-control study and conducted replication study in a Vietnamese case-control study. Methods: Study populations of 101 cases and 391 controls were selected from the Korean Multicenter Cancer Cohort which was constructed from 1993 to 2004. For replication study, Vietnamese hospital-based case-control subjects of 222 cases and 206 controls were selected from 2003 to 2007. The concentrations of plasma genistein, daidzein, and enterolactone were quantified by liquid chromatography-mass spectrometry. Logistic regression models were used to compute odds ratios (ORs) and 95% confidence intervals (CIs), and meta-analysis was conducted to estimate combined ORs (CORs) and 95% Cis of Korean and Vietnamese population in 2014. Results: Genistein showed a continual decrease in colorectal cancer risk according to level up of the concentration categories in Korean and Vietnamese population ( P for trend = 0.032, and 0.001, respectively) and a significantly decreased risk was found at the highest concentration of genistein and daidzein (for the highest category compared to the lowest: COR (95% CI) = 0.46 (0.30–0.69), and COR (95% CI) = 0.54 (0.36–0.82)). When the study population was stratified, the beneficial relationship of genistein with colorectal cancer was observed regardless of sex and anatomical subtype. However, enterolacton level was not associated with colorectal cancer risk. Conclusions: High plasma levels of isoflavones had relationship with a decreased risk of colorectal cancer, regardless of different ethnic background.